Desenvolvimento de processo de inoculação com microcarregador Cytoline 1 visando o cultivo de célula CHO-K1 em biorreator de leito fixo - Querino, Marcelo Vargas (2004)
The use of the technology of animal cell culture for the expression of recombinant proteins has been gaining major interest within biotechnology due the obtation of recent efficient medicaments in the chronic diseases. In this work was utilized the recombinant lineage CHO-K1, denominate CHOZMD, anchorage-dependent. It is capable of expressing a disintegrin with antimetastics properties. Knowing the precedent of well performance of fixed bed bioreactors with utilization of microcarriers in large scale animals cells cultures. It was fixed as purpose of this work the definition of a method to prepare of inoculum to this bioreactor utilizing Cytoline 1 commercial macroporous microcarrier in spinner flask. The cultures realized in spinner flasks of 500 mL with Cytoline 1 microcarriers with DMEM medium in range of pH in 7.0 to 7.4. It showed that the electrostatic incompatibility between the cell and the microcarrier matrix composed of polyethylene and silica was responsible by decreased adhesion cell and, consequently, by intense cell death for firsts hours of experiments. In function this was necessary to utilize an inoculum with high cell concentration and a better pH medium control to reach satisfactory results in the culture. Following this strategy was possible to achieve highest maximum specific growth cell rate (μmáx) for the CHOZMD cell of 0.24d-1 while for wild CHO-K1 cell was obtained 0.36d-1, both comparable with other works encounter in the literature. The best value obtained of cell productivity with recombinant cell was of 6,096 cel/mL·h and for wild cell was of 10,596 cel/mL·h The lager concentrations of adherents cells on microcarriers were obtained in this experiments that utilized concentrated inoculums, in the case of recombinant cell was obtained 1.39·106 cel/mL and in the case with wild cell of 1.65·106 cel/mL. For the preparation of an inoculum for a fixed bed bioreactor when prepared in spinner with Cytoline 1 microcarrier recommend: adoption of an inoculum approximate of 2.0·106 cel/mL in exponential growth phase and with rigorous control of pH medium in 7.3.